SURVEY REPORT: A SHIFT FROM TRADITIONAL TOWARD PEER-TO-PEER (P2P) INFORMATION INTEGRATION - Wicaksana, I Wayan Simri (Majalah Ilmiah Matematika Komputer, 2007)
Peer-ta-Peer (P2P) networking is not a new technology, the P2P has been introduced in the end of70's, however the real implementation can be done in last decade synchronize with Internet progress.This literature study will evaluate from some research papers about the progress of P2P in manyaspects. The main emphasize is in information searching and interoperability.Basic idea of P2P arrived from social life which brings to the model of searching information incomputer network model. From the basic P2P model that called pure P2P until the combination ofsome models to find better solution for special condition is discussed in this paper. Characteristic andfunction of P2P in many environments bring as well as the background knowledge in this area. Thispaper can bring contribution in selecting appropriate model of P2P.Keywords: topology, networking